A detailed perspective of water resource management in a dry and water scarce country: The case in Kuwait - Tariq, Muhammad Atiq Ur Rehman; Alotaibi, Rabeeah; Weththasinghe, Kumudu Kaushalya; Rajabi, Zohreh (Frontiers in Environmental Science, 2022)
Kuwait is an arid country with one of the world’s highest consumption rates per capita. It suffers from severe water scarcity. Annual national expenditure on direct water supply and distribution in Kuwait is substantial, which is a burden on the country’s economy. The nation’s dependency on imported food due to water scarcity is also considered a primary political and security concern. These conditions call for much more efficient use and management of water in Kuwait. This study aims to undertake an extensive analysis of the country’s water resources and review current management strategies for better planning and management. The main sources of freshwater in Kuwait are seawater desalination, brackish groundwater, and recycling wastewater. Seawater desalination is the primary source that produces 61% of freshwater for drinking, agriculture, and other water-dependent industries. Other water management measures related to rainfall drainage systems and water supply networks are also employed to better utilize scarce water. Multiple government organizations that enforce several legal frameworks oversee long-term and acute water-related issues. Regional neighbors also face similar climatic conditions to Kuwait and suffer from water scarcity and associated food shortages. Water conservation and cultivating water-efficient crops have been identified as effective measures to overcome this issue. However, due to the small size and dry arid climate in Kuwait, its future is challenging. It must invest in modern, innovative, and effective solutions to preserve the sustainability of its freshwater resources.